Spontaneous heterotopic pregnancy: a case report - Sharma, Shikha; Chandel, Anu Bala; Sharma, Anupam; Ranaut, Aditi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Heterotopic pregnancy is defined as multiple gestation in which intrauterine and extrauterine gestational sacs co-exist. The extra uterine gestational sac is most commonly tubal ectopic pregnancy. We presented case of a 26 years old multigravida who presented to emergency with complaints of pain abdomen and giddiness for 2-3 days. She was at period of gestation (POG) 7 weeks and on clinical examination patient was anxious with mild pallor, mildly tachycardiac and blood pressure (BP) was 90/60 mm of Hg. After thorough clinical examination and sonography diagnosis of heterotopic pregnancy with ruptured tubal ectopic was made. She was taken up for Emergency laparotomy after investigations and consent. Left salpingectomy was done and she was discharged with a single intrauterine live pregnancy on 6th post op day. For early detection of cases of heterotopic pregnancy careful evaluation of adnexa is mandatory in early gestation scan.